Island Pedicle Flap Pada Dinding Hidung Dengan Karsinoma Sel Basal - Mimbar Taufik; Fajri Alratisda (LPPM Universitas Almuslim, 2023)
A flap is a tissue unit that is transferred from one area (donor site) to another area (recipient site) while still maintaining its blood circulatory system. The island pedicle flap, also known as the V-Y flap, is a modified advancement flap. This flap is a very useful reconstruction option for small to intermediate-sized defects. A 69-year-old Acehnese woman with a history of working as a farmer came with complaints of a non-painful nodule on the wall of her left nose for the last 6 months. Based on the history and physical examination, the patient was provisionally diagnosed with nodular type Basal Cell Carcinoma. An excisional surgical was performed, then a pedicle island flap was performed to close the defect. Anatomical pathology examination results concluded basal cell carcinoma. The island pedicle flap technique is one of the surgical techniques that can be an option to close tumor excision defects. This technique offers a one-stage reconstruction with excellent cosmetic results for defects in the nasal wall. The color and texture of the skin after surgery are almost perfect because the flap originates from the skin immediately adjacent to the defect.